Mastery of Indonesian Vocabulary in Autistic Children - Hajrah Hajrah; Mayong Mayong; Muhammad Saleh (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract. Mastery of Indonesian Vocabulary in Autistic Children. This study aims to describe the mastery of nouns, verbs, and adjectives in autistic children at SLB Arnadya Makassar City. The total number of autistic children in SLB Arnadya Makassar City is 6 students. The data sources set were 3 students, namely students whose parents allowed their children to be used as data sources in this study. The data in this study were obtained through picture tests, listening skills, and student assignments. The data obtained were then analyzed by identifying, classifying, describing, and finally drawing conclusions. The results of research on mastering Indonesian vocabulary in autistic children at SLB Arnadya Makassar City in terms of three classes of Indonesian words namely nouns, verbs, and adjectives can be concluded the following three things. First, the mastery of nouns in autistic children at SLB Arnadya Makassar City on the picture, listening, and written test is 97 words (59.87%). Second, the mastery of verbs in autistic children at SLB Arnadya Makassar City on the picture, listening, and written test of 48 words (29.62%). Third, the mastery of adjectives in autistic children at SLB Arnadya Makassar City on a picture test, listening proficiently, and written as many as 17 words (10.49%). Keywords: vocabulary mastery, nouns, verbs, adjectives, autistic children.